Photodynamic Therapy: A Flexi‐PEGDA Upconversion Implant for Wireless Brain Photodynamic Therapy (Adv. Mater. 29/2020). Issue 29 (21st July 2020) - Teh, Daniel Boon Loong; Bansal, Akshaya; Chai, Chou; Toh, Tan Boon; Tucker, Robert Alan Jappy; Gammad, Gil Gerald Lasam; Yeo, Yanzhuang; Lei, Zhendong; Zheng, Xiang; Yang, Fengyuan; Ho, John S.; Bolem, Nagarjun; et al.
Abstract : An upconversion biocompatible implant is the first step of translating decades‐old near‐infrared nanotransducer research into wireless phototherapeutic devices that can be implanted underneath the skin. The use of a hydrogel and cladding results in an upconversion optical fiber that is able to upconvert in a flexible manner and even transmit NIR at maximal bending is described by Kah‐Leong Lim, Yong Zhang, Brian K. Kennedy, and co‐workers in article number 2001459 . This concept is applicable to various needs of wireless phototherapeutics. With better designs in the future, upconversion implants will be able to be translated from the bench to the bedside.